Spatial distribution and esterase activity in populations of Aedes (Stegomyia) aegypti (Linnaeus) (Diptera: Culicidae) resistant to temephos - Wanessa Porto Tito Gambarra; Walter Fabrício Silva Martins; Maurício Lilioso de Lucena Filho; Ingredy Meneses Cavalcanti de Albuquerque; Otávia Karla dos Santos Apolinário; Eduardo Barbosa Beserra (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
INTRODUCTION: The need for studies that describe the resistance patterns in populations of Aedes aegypti (Linnaeus) in function of their region of origin justified this research, which aimed to characterize the resistance to temephos and to obtain information on esterase activity in populations of Aedes aegypti collected in municipalities of the State of Paraíba. METHODS: Resistance to temephos was evaluated and characterized from the diagnostic dose of 0.352mg i.a./L and multiple concentrations that caused mortalities between 5% and 99%. Electrophoresis of isoenzymes was used to verify the patterns of esterase activity among populations of the vector. RESULTS: All populations of Aedes aegypti were resistant to temephos, presenting a resistance rate (RR) greater than 20. The greatest lethal dose 50% of the sample (CL50) was found for the municipality of Lagoa Seca, approximately forty-one times the value of CL50 for the Rockefeller population. The populations characterized as resistant showed two to six regions of α and β-esterase, called EST-1 to EST-6, while the susceptible population was only seen in one region of activity. CONCLUSIONS: Aedes aegypti is widely distributed and shows a high degree of resistance to temephos in all municipalities studied. In all cases, esterases are involved in the metabolism and, consequently, in the resistance to temephos.